TGF-β in hepatic stellate cell activation and liver fibrogenesis: updated 2019 - Dewidar, Bedair; Meyer, Christoph; Dooley, Steven; Meindl-Beinker, Nadja M. (Cells, 2019)
Liver fibrosis is an advanced liver disease condition, which could progress to cirrhosis and hepatocellular carcinoma. To date, there is no direct approved antifibrotic therapy, and current treatment is mainly the removal of the causative factor. Transforming growth factor (TGF)-β is a master profibrogenic cytokine and a promising target to treat fibrosis. However, TGF-β has broad biological functions and its inhibition induces non-desirable side effects, which override therapeutic benefits. Therefore, understanding the pleiotropic effects of TGF-β and its upstream and downstream regulatory mechanisms will help to design better TGF-β based therapeutics. Here, we summarize recent discoveries and milestones on the TGF-β signaling pathway related to liver fibrosis and hepatic stellate cell (HSC) activation, emphasizing research of the last five years. This comprises impact of TGF-β on liver fibrogenesis related biological processes, such as senescence, metabolism, reactive oxygen species generation, epigenetics, circadian rhythm, epithelial mesenchymal transition, and endothelial-mesenchymal transition. We also describe the influence of the microenvironment on the response of HSC to TGF-β. Finally, we discuss new approaches to target the TGF-β pathway, name current clinical trials, and explain promises and drawbacks that deserve to be adequately addressed.